PROSPEK PENGEMBANGAN LINGUISTIK DAN POTENSI KARIER LINGUIS - Wijaya, Ganjar Harimansyah (Masyarakat Linguistik Indonesia, 2021)
This paper describes the prospects of the development of linguistics from a diachronic aspect with its various streams as well as the potential for interdisciplinary linguistics. Aspects of linguistic development start from structural to cognitive streams. The interdisciplinary nature of linguistics can be seen from the development of linguistics and its relationship with other disciplines. These developments have provided new insights for the branches of linguistics and, as a result, new research methods have emerged. This paper mainly points out the promising prospects for linguistic development in the realm of research and career as a linguist.